Improvement in performance of polysulfone membranes through the incorporation of chitosan-(3-phenyl-1h-pyrazole-4-carbaldehyde). Issue 1 (1st January 2017) - Balakrishna Prabhu, K.; Saidutta, M.B.; Isloor, Arun M.; Hebbar, Raghavendra
Abstract: Pure polysulfone membranes are known to exhibit poor permeability, and high fouling. This study was conducted to explore the possibility of improving the permeation characteristics of polysulfone membranes by using a chitosan derivative as an additive. Polysulfone membranes blended with chitosan derivative 3-phenyl-1H-pyrazole-4-carbaldehyde (ChD) were prepared by the method of wet coagulation. The hydroxyl, amine and the imine functional groups present in the ChD evidently increased the hydrophilicity of the surface of the blended membranes which was confirmed by contact angle measurements. The contact angle of the blended membrane having 2 wt.% ChD was 62 ± 1 as compared to 70 ± 1 of neat polysulfone membrane. The SEM analysis of the blended membranes revealed a highly porous structure with a very thin surface skin layer, finger like projections in the sub-layer with a macro void structure at the base. The blended membranes also showed significant improvement in pure water flux of 351 L m −2 h −1 at 0.8 MPa trans membrane pressure (TMP) as compared to 24 L m −2 h −1 of neat polysulfone membrane at the same TMP. The anti-fouling test using bovine serum albumin exhibited improved anti-fouling characteristic of blended membranes with a maximum flux recovery ratio (FRR) of 57%. The heavy metal rejection study revealed that membrane P-1 showed maximum 36 and 29% rejection for Pb and Cu respectively.